Cementless modular total hip arthroplasty: a retrieval analysis. (28th January 2009) - Paliwal, Manish; Allan, D. Gordon; Filip, Peter
This paper reports the analysis of a modular S-ROM hip implant, which was retrieved at revision, secondary to aseptic loosening approximately after 24-months of implantation. Microscopic analysis confirmed the presence of pitting, fretting corrosion, plastic deformation, and stress induced corrosion cracking. Energy-dispersive x-ray microanalysis of the stem surface revealed the release of metal ions. High resolution inductively coupled plasma mass spectroscopy confirmed elevated titanium ion levels (4.66 ppb) in blood serum. Finite element analysis of the implant showed that the micromotion and stress levels were the maximum at the proximal-lateral region of the taper junction, in congruence with the observation.